Development and validation of a patient-report measure of safety climate for general practice. (19th March 2021) - Madden, Caoimhe; Lydon, Sinéad; Murphy, Andrew W; O'Connor, Paul
Abstract: Background: Patients remain an under-utilized source of information on patient safety, as reflected by the dearth of patient-report measures of safety climate, particularly for use in general practice settings. Extant measures are marked by poor coverage of safety climate domains, inadequate psychometric properties and/or lack of consideration of usability. Objective: To develop a novel patient-report measure of safety climate specifically for completion by general practice patients, and to establish the validity, reliability and usability of this measure. Methods: An iterative process was used to develop the safety climate measure, with patient and general practitioner input. A cross-sectional design was employed to examine the validity (content, construct and convergent), reliability (internal consistency), and usability (readability and burden) of the measure. Results: A total of 584 general practice patients completed the measure. The exploratory factor analysis identified five factors pertaining to safety climate in general practice: Feeling of Safety with GP; Practice Staff Efficiency and Teamwork; Staff Stress and Workload; Patient Knowledge and Accountability, and; Safety Systems and Behaviours. These factors strongly correlated with two global safety measures, demonstrating convergent validity. The measure showed strong internal consistency, and was considered usable for patients as indicated by readability and duration of completion. Conclusion: Our novel measure of safety climate for use in general practice demonstrates favourable markers of validity, reliability and usability. This measure will provide a mechanism for the patient voice to be heard in patient safety measurement, and to be used to improve patient safety in general practice.